2002
DOI: 10.1002/1099-0682(20021)2002:1<93::aid-ejic93>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of the Axial Co−C and Co−S Bonds in B12 Systems − A Density Functional Study

Abstract: The numerous accurate structural data of cobalamins now available allows us to optimize the geometry of these systems, based on a simplified model by using density functional theory (DFT) calculations. This approach, which reproduces the trend of the experimental distances derived from EXAFS and X-ray crystal structures in the corrin macrocycle, permit us to interpret the electronic properties in the NB3−Co−X axial system. In particular, the results are analyzed for cobalamins containing a sulfur ligand which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 20 publications
5
47
2
Order By: Relevance
“…While the equatorial Co–N eq bonds are slightly overestimated computationally, by up to 0.03 Å, these error values are consistent with those reported previously in the literature for pure DFT calculations of truncated corrinoid models. 31, 32, 3436 The distance between the cobalt ion and the upper axial ligand (R) is accurately reproduced for MeCbl and only slightly underestimated for CNCbl (Δ QM/MM-Xtal = −0.03 Å). In the case of H 2 OCbl + , however, the upper axial Co–O bond is significantly overestimated by our calculations, with Δ QM/MM-Xtal = 0.17 Å.…”
Section: Results and Analysismentioning
confidence: 99%
“…While the equatorial Co–N eq bonds are slightly overestimated computationally, by up to 0.03 Å, these error values are consistent with those reported previously in the literature for pure DFT calculations of truncated corrinoid models. 31, 32, 3436 The distance between the cobalt ion and the upper axial ligand (R) is accurately reproduced for MeCbl and only slightly underestimated for CNCbl (Δ QM/MM-Xtal = −0.03 Å). In the case of H 2 OCbl + , however, the upper axial Co–O bond is significantly overestimated by our calculations, with Δ QM/MM-Xtal = 0.17 Å.…”
Section: Results and Analysismentioning
confidence: 99%
“…Interestingly, the Co–NB3 bond distance for AdoCbl (2.24 Å72) is considerably longer than that for MeCbl (2.16 Å66). Finally, like NOCbl, sulfitocobalamin (SO 3 Cbl) also has a longer Co–NB3 bond distance (2.13–2.15 Å73,74) compared with other Cbls with β-axial inorganic ligands. The longer Co–NB3 for SO 3 Cbl and NOCbl can be attributed to the strong σ donor properties of these ligands, in addition to NO being a moderately good π acceptor ligand 75…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that a cobalamin will usually coordinate an ambident nucleophile through the softer of the two potential donor atoms, as in SeCN À , NO 2 À and S 2 O 3 2À [3]. SO 3 2À is S-bound as in sulfito-cobalamin [67,68]. An exception we found was SCN À which is N-bound in the solid state; however, we obtained NMR evidence to show that in solution it existed as a nearly equal mixture of two species which we took to be the N-and S-bound thiocyanato complexes.…”
Section: Discussionmentioning
confidence: 99%